1985
DOI: 10.1139/t85-028
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductivity of natural clays permeated with simple liquid hydrocarbons

Abstract: The hydraulic conductivity, k, of clayey soils is strongly influenced by the physicochemical properties of permeating liquid hydrocarbons. Tests on natural Sarnia soils mixed with pure liquids at a void ratio of 0.8 yielded k values that increased from 5 × 10−9 to 1 × 10−4 cm/s as the dielectric constant of the permeant decreased from 80 to 2.Sequential permeation of compacted, water-wet samples (k ≈ 10−8 cm/s) showed no changes in hydraulic conductivity when permeated with water-insoluble hydrocarbons of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
5

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(72 citation statements)
references
References 5 publications
2
62
0
5
Order By: Relevance
“…In particular, Fernandez and Quigley (1985) for example showed that soil hydraulic characteristics can alter PAH adsorption sites, such that when the soil is too wet the adsorption is driven by soil organic matter content, while in the dry situations clay content has the major role to adsorb the substances (Chiou and Shoup, 1985). With the presence of hydrocarbons in soil, generally, the limitations will be poor moisture-holding capacity (due to hydrophobicity), low permeability (due to clogging) and nutrient deficiencies (because of adsorption and toxicity).…”
Section: Phytoremediation Of Hc and Soil Moisture Statusmentioning
confidence: 99%
“…In particular, Fernandez and Quigley (1985) for example showed that soil hydraulic characteristics can alter PAH adsorption sites, such that when the soil is too wet the adsorption is driven by soil organic matter content, while in the dry situations clay content has the major role to adsorb the substances (Chiou and Shoup, 1985). With the presence of hydrocarbons in soil, generally, the limitations will be poor moisture-holding capacity (due to hydrophobicity), low permeability (due to clogging) and nutrient deficiencies (because of adsorption and toxicity).…”
Section: Phytoremediation Of Hc and Soil Moisture Statusmentioning
confidence: 99%
“…és a fázisok közötti kölcsön-hatások (duzzadási-zsugorodási folyamatok, hiszterézis jelenségek, dezaggregáció, repedések keletkezése stb.) következtében (FERNANDEZ & QUIGLEY, 1985;LENHARD & BROOKS, 1985;BRADFORD & LEIJ, 1995;GRABER & MINGELGRIN, 1998;RUBIN et al, 1998;DICARLO et al, 2000;MAKÓ & HERNÁDI, 2012;ASGARZADEH, et al, 2014). Mikromorfometriai vizsgálatok (pl.…”
Section: A Pórusszerkezet Megváltozása Víz/szerves Folyadék/szilárd Funclassified
“…Consolidation due to a difference in chemical composition of the pore water was investigated by Fernandez & Quigley (1985, 1991 and later by Hueckel (1997) and Boukpeti et al (2004). They studied the influence of a single organic contaminant on the compressibility properties of Sarnia clay, which is an Na-montmorillonite with traces of Ca-smectite.…”
Section: Theories and Evidencementioning
confidence: 99%